2014
DOI: 10.1097/nmd.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Self-Esteem and Perfectionism in Anorexia Nervosa and Body Dysmorphic Disorder

Abstract: Previous studies have identified phenotypic similarities between anorexia nervosa (AN) and body dysmorphic disorder (BDD), which share the common feature of negative body image. Studies comparing endophenotypes that may cut across both disorders-as suggested by the National Institute of Mental Health's Research Domain Criteria-are limited. Sixty-nine individuals (AN, n = 24; BDD, n = 23; mentally healthy controls [MHCs], n = 22) completed diagnostic interviews and self-reports assessing self-esteem and perfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 40 publications
(71 reference statements)
4
26
0
1
Order By: Relevance
“…Reflecting perfectionistic concerns and checking of detail (Stairs et al, 2012), that was uniquely predictive. These findings are consistent with the BDD and eating disorder literature, in which doubts about actions were higher in the clinical groups compared to controls (Buhlmann, Etcoff et al, 2008;Hartmann et al, 2015). Thus, it is possible that detailed checking is a pervasive symptom characteristic of T A B L E 1 Descriptive statistics and Pearson r correlations for perfectionism, dot-probe, dysmorphic concern, depression, anxiety, and stress scores .63** Indicates where one item from the DASS-21 anxiety scale produced an item-total correlation of .35 but was retained for conceptual relevance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Reflecting perfectionistic concerns and checking of detail (Stairs et al, 2012), that was uniquely predictive. These findings are consistent with the BDD and eating disorder literature, in which doubts about actions were higher in the clinical groups compared to controls (Buhlmann, Etcoff et al, 2008;Hartmann et al, 2015). Thus, it is possible that detailed checking is a pervasive symptom characteristic of T A B L E 1 Descriptive statistics and Pearson r correlations for perfectionism, dot-probe, dysmorphic concern, depression, anxiety, and stress scores .63** Indicates where one item from the DASS-21 anxiety scale produced an item-total correlation of .35 but was retained for conceptual relevance.…”
Section: Discussionsupporting
confidence: 90%
“…Both types of perfectionism were found to be important risk factors for eating disorders. There are some discrepant findings concerning the specific subtypes of perfectionism characteristic of BDD, with one study (Hartmann, Thomas, Greenberg, Matheny, & Wilhelm, 2015) finding that compared to controls, the eating disorder and BDD group endorsed higher perfectionistic strivings and concerns. Conversely, in a related study comprised of BDD and OCD participants (Buhlmann, Etcoff, & Wilhelm, 2008), compared to controls, the treatment groups differed on perfectionistic concerns only.…”
Section: Perfectionismmentioning
confidence: 99%
“…Again, differences between groups were not detected (Jacobi et al, 2004). However, in each case, one study demonstrated that AN patients had significantly lower self-esteem scores than patients with a purging disorder with loss of control and body dysmorphic disorder (Goldschmidt et al, 2016;Hartmann et al, 2014).…”
Section: Differences Between Individuals With An and Individuals Wimentioning
confidence: 92%
“…Only one study compared individuals with AN to those with a binge-eating disorder. However, in each case, one study demonstrated that AN patients had significantly lower self-esteem scores than patients with a purging disorder with loss of control and body dysmorphic disorder (Goldschmidt et al, 2016;Hartmann et al, 2014). However, in each case, one study demonstrated that AN patients had significantly lower self-esteem scores than patients with a purging disorder with loss of control and body dysmorphic disorder (Goldschmidt et al, 2016;Hartmann et al, 2014).…”
Section: Differences Between Individuals With An and Individuals Wimentioning
confidence: 97%
“…Recruitment and participant selection was performed for a larger project and a comparable description can be found in other studies from this project (Hartmann et al, 2013;Hartmann et al, 2014). We recruited participants for all groups through flyers and advertisement (n¼ 37), intakes in outpatient clinics (n¼ 24), and residential settings (n¼ 15).…”
Section: Participantsmentioning
confidence: 99%